Chromosomal mapping of genetic loci associated with non-insulin dependent diabetes in the GK rat. - Gauguier, D; Froguel, P; Parent, V; Bernard, C; Bihoreau, M; Portha, B; James, MR; Penicaud, L; Lathrop, M; Ktorza, A (1996)
Goto-Kakizaki (GK) rats are a well characterized model for non-insulin dependent diabetes mellitus (NIDDM). We have used a combination of physiological and genetic studies to identify quantitative trait loci (QTLs) responsible for the control of glucose homeostasis and insulin secretion in a F2 cohort bred from spontaneously diabetic GK rats. The genetic dissection of NIDDM allowed us to map up to six independently segregating loci predisposing to hyperglycaemia, glucose intolerance or altered insulin secretion, and a seventh locus implicated in body weight. QTLs implicated in glucose tolerance and adiposity map to the same region of rat chromosome 1, and may indicate the influence of a single locus. Our study demonstrates that distinct combinations of genetic loci are responsible for different physiological characteristics associated with the diabetic phenotype in the GK rat, and it constitutes an important step for directing the search for the genetic factors involved in human NIDDM.